Inflammatory and cardiac biomarkers in pulmonary arterial hypertension: The prognostic role of IL-34 - Bolayır, Hasan Ata; Karasu, Mehdi; Gelen, Mehmet Ali; Akın, Yusuf; Çeçen, Erkan; Küçük, Uğur; Bulu, Aykut (Elsevier Inc., 2025)
Background: Pulmonary arterial hypertension (PAH) is characterized by increased pulmonary artery pressure with significant morbidity and mortality. Inflammatory processes are crucial in PAH pathogenesis, with inflammatory cells and mediators present early in disease progression. IL-34 involvement in inflammatory pathways suggests that IL-34 could be an important player in the progression of PAH, influencing both pulmonary pressures and vascular changes. Objective: The purpose of this study was to investigate the correlation between IL-34 levels and pulmonary arterial hypertension (PAH), aiming to enhance the understanding of the molecular mechanisms underlying PAH and explore IL-34?s potential as a biomarker. Methods: Consecutive PAH patients diagnosed via right-heart catheterization at Malatya Turgut Ozal Eğitim ve Araştırma Hastanesi (Dec 2022 - Apr 2024) were enrolled. Patients were classified into low-risk and high-risk groups based on comprehensive risk assessments that included clinical parameters, hemodynamic measurements and biomarkers, in-line with ESC/ERS guidelines. Serum IL-34, hs-CRP, and NT-proBNP levels were measured and compared with those of healthy controls. Echocardiographic assessments and statistical analyses, including ROC analysis, were conducted to evaluate biomarker significance and predictive capabilities. Results: The mean age of low-risk and high-risk PAH patients was 42 ± 7.2 years and 45 ± 5.5 years, respectively. The mean age of the control group was 40 ± 6.4 years. Males comprised 54.29 % of the low-risk group, 56 % of the high-risk group, and 53.3 % of the control group. IL-34 and hs-CRP levels were significantly elevated in PAH patients compared to controls. IL-34 correlated positively with systolic pulmonary artery pressure, RA area, and NT-proBNP levels. Multivariate analysis revealed that IL-34 and hs-CRP were independent predictors of PAH. IL-34 levels>29.8 pg/mL predicted PAH with 78 % sensitivity and 69 % specificity, while levels >44.4 pg/mL predicted high-risk PAH with 84 % sensitivity and 77 % specificity. Conclusion: Elevated IL-34 and hs-CRP levels are associated with PAH severity and right ventricular dysfunction, suggesting IL-34?s potential as a diagnostic and prognostic biomarker. Further research is needed to validate these findings and explore IL-34-targeted therapies in pH management. © 2024 Elsevier Inc.
Keywords: Biomarkers; IL-34; Inflammation; Pulmonary arterial hypertension (PAH); Right Ventricular Dysfunction